Bilingualism in Bangladeshi education: : The underlying problems and confusions - Faheem Hasan Shahed; Mohammad Mosiur Rahman (Celebes Journal of Language Studies, 2022)
While English overwhelms a section of the Bangladeshi society by virtue of its ‘power and prestige’ factors, it has consolidated its position in the academic domains preserving its ‘fear and resentment’ aspects. Academic authorities demand producing considerable ‘English-knowing’ graduates every year, but a generic apprehension persists that these graduates can hardly meet the challenges of the white-collar local job markets. This apprehension proves that the stature of English is trapped inside an obscure policymaking. If we underscore the concern, also articulated by Pennycook (2002) for constant reciprocity between globalization and localization to avoid the hegemonic influence of English, we might be interested in critically reassessing the issue of bilingualism in our context based on this simple query: should bilingualism be imposed on all Bangladeshis? At the same time, given the falling standard of Bangla proficiency, the imperialism of English—as defined by Phillipson (1992)—also demands attention. Incorporating critical lenses of language planning and bilingualism and bilingual education, based on the content analysis of secondary sources such as published literature and expert opinions, we attempted to highlight the association of power and prestige with English leading to its imposition on Bangladeshi education system.